Comparative study of biogas production with cow dung and kitchen waste in Fiber-Reinforced Plastic (FRP) biodigesters. (2022) - Glivin, Godwin; Mariappan, V.; Premalatha, M.; Hareesh Krishnan, H.; Joseph Sekhar, S.
Abstract: A performance study was conducted with two 1 m 3 capacity anaerobic digester for producing biogas from cow dung and kitchen waste. The entire structure was constructed of fiber-reinforced plastic. Following construction and assembly, the biogas digestion unit was checked for 30 days to ensure the digester's success for both biowastes. In each digester, 2.5 kg cow dung and kitchen waste was diluted with water in the ratio 1:1 and subjected to a fourty five days retention time to prepare a slurry of 15% and 20% total solid. Results presented an average per day gas yield of 0.35 m 3 for cow dung and 0.20 m 3 for the kitchen waste at an average substrate temperature of 32 °C while the daily ambient temperatures varied from 29 °C to 31 °C and a pH of 6.50 to 7.40 for the cow dung and 4.91 to 7.1 for the kitchen waste.